Acoustical and optical radiation pressure and the development of single beam acoustical tweezers. (July 2017) - Thomas, Jean-Louis; Marchiano, Régis; Baresch, Diego
Abstract: Studies on radiation pressure in acoustics and optics have enriched one another and have a long common history. Acoustic radiation pressure is used for metrology, levitation, particle trapping and actuation. However, the dexterity and selectivity of single-beam optical tweezers are still to be matched with acoustical devices. Optical tweezers can trap, move and position micron size particles, biological samples or even atoms with subnanometer accuracy in three dimensions. One limitation of optical tweezers is the weak force that can be applied without thermal damage due to optical absorption. Acoustical tweezers overcome this limitation since the radiation pressure scales as the field intensity divided by the speed of propagation of the wave. However, the feasibility of single beam acoustical tweezers was demonstrated only recently. In this paper, we propose a historical review of the strong similarities but also the specificities of acoustical and optical radiation pressures, from the expression of the force to the development of single-beam acoustical tweezers. Abstract : Highlights: Studies on radiation pressure in acoustics and optics have enriched one another and have a long common history. Acoustic radiation pressure is used for metrology, levitation, particle trapping and actuation. However, the dexterity and selectivity of single-beam optical tweezers are still to be matched with acoustical devices. Optical tweezers can trap, move and positioned micron size particles with subnanometer accuracy in three dimensions. One limitation of optical tweezers is the weak force that can be applied without thermal damage due to optical absorption. Acoustical tweezers overcome this limitation since the force scales as the field intensity divided by its propagation speed. However, the feasibility of single beam acoustical tweezers was demonstrated only recently. We propose a review of the strong similarities but also the specificities of acoustical and optical radiation pressures.